Perancangan Interior Restoran The Roaring Twenties & Speakeasy Bar di Surabaya - Selvia Cen; Stephanus P Honggowidjaja; purnama esa dora tedjokoesomo (Intra, 2016)
This design works will design The Roaring Twenties & Speakeasy Bar Restaurant with American style in the 1920s. The advance of the urban lifestyle demands that people get more entertainment to release stress and busyness. Places for entertainment are most visited by the public are restaurant and lounge. With the services and food dishes that visitors can feel comfortable. Many various types of restaurants, lounges and bars according to the Author still can’t adequately meet the needs of society. In this restaurant, the concept will be used by the author in designing the restaurant The Roaring Twenties & Speakeasy Bar is a classic and stately using the Art Deco style. Author using design thinking as design process. Author conducted observations and interviews of similar restaurants and also to the visitor of the restaurant. This restaurant not only serves food, but also able to relax linger and socialize with around while enjoying live music and serving snacks at the lounge and bar. Classy and magnificent concept is intended which when visitors arrive can immediately feel the splendid in the days of the 1920s.